2019
DOI: 10.1002/ajb2.1377
|View full text |Cite
|
Sign up to set email alerts
|

Genome duplication effects on functional traits and fitness are genetic context and species dependent: studies of synthetic polyploid Fragaria

Abstract: Premise Divergence in functional traits and adaptive responses to environmental change underlies the ecological advantage of polyploid plants in the wild. While established polyploids may benefit from combined outcomes of genome doubling, hybridization, and polyploidy‐enabled adaptive evolution, whether genome doubling alone can drive ecological divergence or whether the outcome is genetically variable remains less clear. Methods Using synthetic, colchicine‐induced, autotetraploid (4x) plants derived from self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 92 publications
(210 reference statements)
11
42
0
Order By: Relevance
“…Traditionally, agriculture and horticulture have benefited from the use of natural or artificial polyploid genotypes with increased tolerance to stresses such as salinity or drought. Herbaceous polyploid genotypes with these characteristics are present in species with genera of agronomic interest, such as Fragaria (Wei et al., 2019, 2020), Lycopersicum (Tal and Gardi, 1976) or Raphanus (Pei et al., 2019), but also in genera with ornamental species such as Chamaenerion (Maherali et al., 2009), Phlox (Vyas et al., 2007) or Saxifraga (Decanter et al., 2020). Comparatively, polyploidy is less frequent in woody species (Meyers and Levin, 2006), but some results in woody plants point to the capacity of tetraploids to retain more water, such as in seedlings of Betula (Li et al., 1996), and plants of Lonicera (Li et al., 2009) or Populus (Xu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, agriculture and horticulture have benefited from the use of natural or artificial polyploid genotypes with increased tolerance to stresses such as salinity or drought. Herbaceous polyploid genotypes with these characteristics are present in species with genera of agronomic interest, such as Fragaria (Wei et al., 2019, 2020), Lycopersicum (Tal and Gardi, 1976) or Raphanus (Pei et al., 2019), but also in genera with ornamental species such as Chamaenerion (Maherali et al., 2009), Phlox (Vyas et al., 2007) or Saxifraga (Decanter et al., 2020). Comparatively, polyploidy is less frequent in woody species (Meyers and Levin, 2006), but some results in woody plants point to the capacity of tetraploids to retain more water, such as in seedlings of Betula (Li et al., 1996), and plants of Lonicera (Li et al., 2009) or Populus (Xu et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Polyploids can achieve faster climatic niche differentiation than their diploid progenitors, possibly facilitating polyploid speciation (Baniaga et al, 2020). In comparisons of diploids and chemically induced polyploids of the same species, polyploids showed changes in physiologically‐relevant cellular traits, such as vein density, but did not exhibit concomitant changes in ecologically relevant responses, such as heat stress response or growth rate (Wei et al, 2020). In previous studies, increases in genome size have been correlated with slower growth rate (Cavalier‐Smith, 1978; Sharpe et al, 2012; Müller et al, 2019), which could in turn limit plants with large genomes from colonizing stressful or seasonal environments with short growing seasons where fast growth is required (Knight et al, 2005; Qiu et al, 2019).…”
mentioning
confidence: 99%
“…The authors expanded on previous work that identified the role of the mutant phyA in the BOG response by identifying a new mutant, sig6, which like phyA, allowed for greening after treatment that should have induced BOG. Finally, Wei et al (2020) examined the types and patterns of trait changes that may occur when genomes double, which can allow for rapid evolutionary adaptation to new and stressful environments. Using synthetic Fragaria polyploids, they show that genome doubling alters traits such as stomatal length and density, as well as specific leaf area and vein density.…”
Section: Stressful Interactionsmentioning
confidence: 99%